The level of psychological rebellion among adolescent students in middle school. - Mayali, Soumia; Meddour , Malika (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
This study aimed to identify the level of psychological rebellion among adolescent students in middle school in some middle schools in the city of Biskra, as well as to identify whether there were differences in its level according to the variables of gender (male, female) and academic achievement (weak, average, high) for the first and second semesters, for the academic year (2023/2024), and for this the researchers used the descriptive comparative approach as the most appropriate method for the study, as well as the psychological rebellion scale (prepared by the researchers), as the study sample included (319) male and female students (159 males), (160 females) between the ages of 14 and 16 years, who were selected randomly, distributed over four middle schools in the city of Biskra from the third and fourth middle levels. After presenting and analyzing the statistical data, the results of the study concluded that the level of psychological rebellion among the individuals of the study sample is at a low level, with the discovery of statistically significant differences in psychological rebellion attributed to the gender variable in favor of males, and also the existence of statistically significant differences attributed to the variable of academic achievement in favor of those with low academic achievement. The researchers used a set of statistical treatments such as arithmetic averages, the (t) test and the one-way variance test (F) to detect the differences, the Scheffe test and the Statistical Package for Social Sciences (SPSS) program. The study concluded with some recommendations and proposals, including activating the role of school and vocational guidance and counseling consultants to prevent and reduce the problem, whether through individual or group counseling, and raising awareness of the seriousness of the problem, especially in adolescence, through communication with the family, teachers and all active parties for the necessity of integrated work.